A long-lasting eruption heralds SN 2023ldh, a clone of SN 2009ip - Pastorello, A.; Reguitti, A.; Tartaglia, L.; Valerin, G.; Cai, Y.-Z.; Charalampopoulos, P.; De Luise, F.; Dong, Y.; Elias-Rosa, N.; Farah, J.; Farina, A.; Fiscale, S.; et al. (EDP Sciences, 2026)
We discuss the results of the spectroscopic and photometric monitoring of the type IIn supernova (SN) 2023ldh. Survey archive data show that the SN progenitor experienced erratic variability in the years before exploding. Beginning May 2023, the source showed a general slow luminosity rise that lasted for over four months, with some superposed luminosity fluctuations. In analogy to SN 2009ip, we call this brightening 'Event A'. During Event A, SN 2023ldh reached a maximum absolute magnitude of M-r = -15.52 +/- 0.24 mag. The light curves then decreased by about 1 mag in all filters for about two weeks reaching a relative minimum, which was followed by a steep brightening (Event B) to an absolute peak magnitude of M-r = -18.53 +/- 0.23 mag, replicating the evolution of SN 2009ip and similar to that of type IIn SNe. The three spectra of SN 2023ldh obtained during Event A show multi-component P Cygni profiles of H I and Fe II lines. During the rise to the Event B peak, the spectrum shows a blue continuum dominated by Balmer lines in emission with Lorentzian profiles, with a full width at half maximum velocity of about 650 km s(-1). Later, in the post-peak phase, the spectrum reddens, and broader wings appear in the H alpha line profile. Metal lines with P Cygni profiles and velocities of about 2000 km s(-1) are clearly visible. Beginning around three months past maximum and until very late phases, the Ca II lines become among the most prominent features, while H alpha is dominated by an intermediate-width component with a boxy profile. Although SN 2023ldh mimics the evolution of other SN 2009ip-like transients, it is slightly more luminous and has a slower photometric evolution. The surprisingly homogeneous observational properties of SN 2009ip-like events may indicate similar explosion scenarios and similar progenitor parameters.